2011
DOI: 10.1094/pdis-04-10-0298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Botrytis cinerea Isolates Present in Thompson Seedless Table Grapes in the Central Valley of Chile

Abstract: Botrytis cinerea isolates from flowers and berries of Vitis vinifera ‘Thompson seedless’ (grapevine) were characterized in terms of two transposable elements (TEs) Boty and Flipper, random amplified polymorphic DNA (RAPD), infection levels, and resistance to iprodione. The isolates were collected from grapevines under fungicide programs of variable numbers of iprodione applications, and replicated in three Chilean Central Valley locations. Recovery was repeated from clusters collected at four phenological stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
6
30
0
Order By: Relevance
“…The other isolate types found in our samples were: boty isolates (21.2%), flipper isolates (9.1%), and vacuma isolates (6.1%). This result was in agreement with previous studies that had demonstrated the significant predominance of transposa type [19] [45]- [47]. Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The other isolate types found in our samples were: boty isolates (21.2%), flipper isolates (9.1%), and vacuma isolates (6.1%). This result was in agreement with previous studies that had demonstrated the significant predominance of transposa type [19] [45]- [47]. Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, molecular studies of different nuclear genes have suggested that B. cinerea populations are grouped into two different clades: group I and group II, phylogenetic species [13] [14]. Described group I isolates are exclusively from the vacuma transposon type, while group II can feature transposa, flipper (containing only flipper), boty (containing only boty) or vacuma genotype [8] [9] [13] [15]- [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, predominance of a certain type appears to be influenced by the host. While on grapes, strawberries and tomatoes, Transposa types are predominant, whereas B. cinerea populations from kiwi and apples are dominated by Vacuma types (Esterio et al 2011;Johnston et al 2013;Muñoz et al 2002;Samuel et al 2012;M. Hahn, unpublished).…”
Section: Species Identification and Numbersmentioning
confidence: 99%
“…Isolates carrying either Boty or Flipper in the B. cinerea genome have also been described (De Miccolis Angelini et al, 2003;Giraud et al, 1999;Muñoz, et al, 2002). In addition, the presence of Boty and Flipper has been found in Chilean populations of B. cinerea that affect table grapes, and transposa is the most common isolate (Esterio et al, 2011). However, the presence of transposon elements in B. cinerea appears to be independent of the ability of the organism to cause infection (Ciliberti et al, 2015a).…”
Section: Survival Inoculum Sources and Dispersalmentioning
confidence: 99%